جدید اخلاقی بحران کی فکری بنیادیں: The Intellectual Foundations of the Modern Ethical Crisis - Dr Muhammad Rasheed Arshad (AL-IDRAK JOURNAL, 2024)
The modern world is full of issues and diseases of all types. The moral crises of the modern world are among the deadliest diseases. The greatest obstacle facing religion, after faith, is ethics. This article makes an effort to comprehend the historical context and intellectual foundations of these moral dilemmas. Comprehending the theoretical underpinnings of these problems is crucial for promptly identifying and resolving societal issues. Although ideas and theories have external influences, it can be difficult to determine how these factors affect societal and cultural contexts. Thus, in order to fully comprehend and address urgent societal concerns, a critical analysis of important ideas and theories is required.